(untitled) (Revista Electrónica REDINE, 2021)
This review describes the process of creation and consolidation of the scientific journal "Bioagro" (ISSN 2521-9693) of the Universidad Centroccidental Lisandro Alvarado, Venezuela. This means of scientific dissemination was founded in 1982, attached to the Dean of Agronomy of said university, published every four months, the purpose of which is to contribute to the dissemination of scientific articles by national and international researchers on agricultural science topics.